Sex differences in responding to rectal cancer symptoms - RISTVEDT, STEPHEN L. (2008)
Many people who develop cancer symptoms wait inordinate amounts of time before seeking medical attention. Studies have found that symptom appraisal time - the time that passes before the individual concludes that their symptoms could be serious - accounts for most of the total delay time across subjects. It is thus important to understand the individual characteristics associated with slow recognition of dangerous symptoms. In this study, 62 patients (38 males) recently diagnosed with rectal cancer answered questions regarding the development of symptoms as well as their decisions and behaviors prior to seeking help. One subgroup of patients - males with the lowest scores on a measure of trait anxiety - took significantly longer to recognize the seriousness of their symptoms as compared to all other patients. This finding is discussed in the context of recent studies where the interaction of sex and negative affect is related to symptom reporting and other health-related behaviors.